Exploring the length of the common channel of pancreaticobiliary maljunction on magnetic resonance cholangiopancreatography. (19th September 2014) - Itokawa, Fumihide; Kamisawa, Terumi; Nakano, Toshiaki; Itoi, Takao; Hamada, Yoshinori; Ando, Hisami; Fujii, Hideki; Koshinaga, Tsugumichi; Yoshida, Hitoshi; Tamoto, Eiji; Noda, Takuo; Kimura, Yasutoshi; et al.
Abstract Background In the revised diagnostic criteria for pancreaticobiliary maljunction (PBM), PBM can be diagnosed from a long common channel by magnetic resonance cholangiopancreatography (MRCP). However, it is necessary to differentiate from high confluence of pancreaticobiliary ducts (HCPBD) with a relatively long common channel (≥6 mm) and effect of the sphincter in the pancreaticobiliary junction. This multicenter study aimed to explore definite value of the length of an abnormally long common channel, which enables to distinguish PBM from HCPBD on MRCP. Methods In 184 PBM patients and 22 HCPBD patients who were diagnosed by direct cholangiography and underwent MRCP, the length of the common channel was measured. Results The length of the common channel was 16.2 ± 6.9 mm on direct cholangiography and 13.9 ± 6.2 mm on MRCP in PBM patients, and 7.7 ± 1.5 mm and 6.6 ± 1.4 mm in HCPBD patients. The optimal cut off value of the length of the common channel to distinguish PBM from HCPBD was identified to be 9 mm. Conclusions Pancreaticobiliary maljunction can be diagnosed from an abnormally long common channel on MRCP, but in cases of the common channel ≤9 mm on MRCP, direct cholangiography is needed to confirm PBM.